2003
DOI: 10.1007/bf03402041
|View full text |Cite|
|
Sign up to set email alerts
|

Profiling of Hodgkin’s Lymphoma Cell Line L1236 and Germinal Center B Cells: Identification of Hodgkin’s Lymphoma-specific Genes

Abstract: The malignant cells of classical Hodgkin's lymphoma (cHL), Hodgkin and Reed-Sternberg (HRS) cells, appear to be derived from germinal center (GC) B cells in most cases of the disease. Apart from recent findings of constitutive activation of some transcription factors and autocrine stimulation by cytokine receptors, the mechanisms of malignant transformation in cHL still remain poorly understood. We performed a large scale gene expression study using serial analysis of gene expression (SAGE), comparing the cHL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 64 publications
1
34
0
Order By: Relevance
“…3 Subsequently, many scholars found that PRL-3 was highly expressed in many tumours, such as breast cancer, ovarian cancer, intestinal cancer, gliomas and stomach cancer, and was closely related to metastasis. 4-8 PRL-3 expression has also been reported in a Hodgkin's lymphoma cell line, 9 melanomas, liver, ovarian, breast and gastric cancers, where its presence seems to have an important role in the acquisition of metastatic potential of tumour cells. 10,11 Consistent with the role of PRL-3 over-expression in metastasis, its ectopic expression in different cell types is correlated with the induction of metastatic phenotypes, such as invasion and motility capabilities.…”
Section: Introductionmentioning
confidence: 91%
“…3 Subsequently, many scholars found that PRL-3 was highly expressed in many tumours, such as breast cancer, ovarian cancer, intestinal cancer, gliomas and stomach cancer, and was closely related to metastasis. 4-8 PRL-3 expression has also been reported in a Hodgkin's lymphoma cell line, 9 melanomas, liver, ovarian, breast and gastric cancers, where its presence seems to have an important role in the acquisition of metastatic potential of tumour cells. 10,11 Consistent with the role of PRL-3 over-expression in metastasis, its ectopic expression in different cell types is correlated with the induction of metastatic phenotypes, such as invasion and motility capabilities.…”
Section: Introductionmentioning
confidence: 91%
“…Elevated expression of PRL-2 in malignancies has been described in pediatric acute myeloid leukemia [35], Hodgkin's lymphoma cells [36], and prostate cancer [37]. PRL-1 overexpression in tumor tissues has been reported less frequently, although the phosphatase was expressed at higher levels in cell lines of melanoma [38] and pancreatic cancer [39].…”
Section: Phosphatases Of Regenerating Livermentioning
confidence: 99%
“…For the dissection of an area of approximately 0.3 cm 2 of tumor tissue, 7-μm thick sections of frozen tissue were cut and stained with H&E essentially as described previously [22]. The tissue was dissected with a scalpel and transferred into a 0.5-ml tube.…”
Section: Tissue Specimensmentioning
confidence: 99%